PENGEMBANGAN SISTEM CERDAS MENGGUNAKAN PENALARAN BERBASIS KASUS (CASE BASED REASONING) UNTUK DIAGNOSA PENYAKIT AKIBAT VIRUS EKSANTEMA - Agus Sasmito Aribowo (Telematika, 2010)
Disease caused by a exanthema virus is a common disease in Indonesia. There are many types of diseases caused by this virus. Examples are chicken pox, measles, variola, etc. with symptoms almost similar to each other. To correctly identify the symptoms  need experts. But the problem is very limited number of experts. Then the expert system is needed which has been given by the expert knowledge to assist in the diagnosis. Expert system in this research uses a case-based reasoning approach. If there is a similar case, the reasoning for considering the case of the nearest using Probabilistic Bayes. The result is the system will still be able to provide the best recommendations solution for new cases based on the solution to an old case that the nearest level of similarity.